Dendritic cells: In the forefront of immunopathogenesis and vaccine development – A review - Mohamadzadeh, Mansour (BioMed Central, 2004)
Dendritic cellls (DCs) comprise an essential component of the immune system. These cells, as antigen presenting cells (APCs) to naïve T cells, are crucial in the initiation of antigen specific immune responses. In the past years, several DC subsets have been identified in different organs which exert different effects in order to elicit adaptive immune responses. Thus, identification of such DC subsets has led to a better understanding of their distribution and function in the body. In this review, several key properties of the immunobiology, immunopathogenesis and vaccine strategies using DCs will be discussed.